Some features of the development of women’s education in Tatar villages in the beginning of the 20th century - Lyalya R. Murtazina; Alsou A. Zinnatullina (Историческая этнология, 2022)
This article is devoted to the analysis of some problems and features of the development of women’s education among the Tatars in the countryside. Women’s schools first appeared in cities. Then they began to open in the Tatar villages. The development of these schools was reflected in the contradictions between the supporters of the old-method teaching and the Jadids. Very often the people were on the side of the former. As a result, women’s schools were forced to close and teachers lost their jobs. In some villages, thanks to the activities of progressive people, schools developed and became famous in Russia. The authors give examples of such schools and teachers. The work uses the publications of the Tatar periodical press of the early 20th century.